2004
DOI: 10.1103/physreve.69.056308
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent transition of thermocapillary flow induced by water evaporation

Abstract: Water has been examined for thermocapillary convection while maintained just outside the mouth of a stainless-steel, conical funnel where it evaporated at different but steady rates. Evaporation at a series of controlled rates was produced by reducing the pressure in the vapor-phase to different but constant values while maintaining the temperature of the water a few millimeters below the interface at 3.56+/-0.03 degrees C in each case. Since water has its maximum density at 4 degrees C, these conditions ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 18 publications
10
94
3
Order By: Relevance
“…Marangoni convection, which arises due to a surface tension gradient at the non-isothermal interface, has been shown to increase the heat transfer rates significantly in many systems [13][14][15]. At low superheats (< 5K), however, it is observed that Marangoni convection does not significantly affect …”
Section: Role Of Bulk Convectionmentioning
confidence: 75%
See 1 more Smart Citation
“…Marangoni convection, which arises due to a surface tension gradient at the non-isothermal interface, has been shown to increase the heat transfer rates significantly in many systems [13][14][15]. At low superheats (< 5K), however, it is observed that Marangoni convection does not significantly affect …”
Section: Role Of Bulk Convectionmentioning
confidence: 75%
“…This causes better mixing and increased heat transfer rates. Marangoni convection under large temperature differences has been shown to have a significant enhancement effect on heat transfer [13,14,15]. Khrustalev and Faghri [16] developed a mathematical model of the evaporating liquid-vapor meniscus in a capillary slot.…”
Section: Introductionmentioning
confidence: 99%
“…31, a spherical coordinate system is used with origin at the center of the meniscus ͑see Fig. 9͒, and a shear stress balance at the interface is performed.…”
Section: B Scaling Analysismentioning
confidence: 99%
“…In (Zhang et al 2007) a thin film of an aqueous binary mixture in a large compartment was examined by the shadow-graph method to show the generation of convection patterns due to vertical temperature gradients. A vertical micro-channel is filled with water at a low temperature, incompatible with cell function, and the deflection of a cantilever is used to measure the thermocapillary flow rate dependent on the vapor-phase pressure (Ward and Duan 2004). Evaporation-induced toroidal convection flows of non-biocompatible solutions (ethanol, methanol, acetone, silicone oil, etc.…”
Section: Introductionmentioning
confidence: 99%